2017
DOI: 10.1111/psyp.13047
|View full text |Cite
|
Sign up to set email alerts
|

Detection of deception: Event‐related potential markers of attention and cognitive control during intentional false responses

Abstract: Successful deception requires the coordination of multiple mental processes, such as attention, conflict monitoring, and the regulation of emotion. We employed a simple classification task, assessing ERPs to further investigate the attentional and cognitive control components of (instructed) deception. In Experiment 1, 20 participants repeatedly categorized visually presented names of five animals and five plants. Prior to the experiment, however, each participant covertly selected one animal and one plant for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 65 publications
(156 reference statements)
1
10
0
Order By: Relevance
“…Neuroimaging studies repeatedly found an increased activation of the ACC during deceptive responses (Langleben et al, 2002(Langleben et al, , 2005Sip et al, 2008). Likewise, ERP studies found larger (more negative) MFN amplitudes for deceptive compared to truthful answers, revealing a greater response conflict for deception (Gibbons et al, 2018;Johnson et al, 2005Johnson et al, , 2008Leue et al, 2012). This is in line with the notion that when responding deceptively, conflicts are prevalent and an inhibition of the truthful response is needed (see Chapter 2.2.…”
Section: Figuresupporting
confidence: 61%
See 2 more Smart Citations
“…Neuroimaging studies repeatedly found an increased activation of the ACC during deceptive responses (Langleben et al, 2002(Langleben et al, , 2005Sip et al, 2008). Likewise, ERP studies found larger (more negative) MFN amplitudes for deceptive compared to truthful answers, revealing a greater response conflict for deception (Gibbons et al, 2018;Johnson et al, 2005Johnson et al, , 2008Leue et al, 2012). This is in line with the notion that when responding deceptively, conflicts are prevalent and an inhibition of the truthful response is needed (see Chapter 2.2.…”
Section: Figuresupporting
confidence: 61%
“…The P300 amplitude is the most prominent ERP analyzed in CIT studies (Leue & Beauducel, 2019;Meijer et al, 2014;Rosenfeld et al, 2013). Yet, some studies also analyzed MFN amplitudes for participants completing the CIT (Gibbons et al, 2018;Leue et al, 2012). They found enlarged MFN amplitudes for probe compared to irrelevant items (Gibbons et al, 2018;Leue et al, 2012).…”
Section: The Concealed Information Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 118 references several primary studies had to be excluded because of the following reasons: (1) k = 13 studies investigated electrodermal parameters (e.g., skin conductance level) or cardiovascular parameters (e.g., heart rate), (2) k = 4 studies investigated EEG frequency band data or connectivity data, (3) k = 9 studies investigated exclusively other stimulus-locked ERPs (e.g., N400 amplitude) or stimulus-locked P300 at occipital sites instead of parietal sites (Gibbons, Schnürch, Wittinghofer, Armbrecht, & Stahl, 2018), (4) k = 9 studies investigated response-locked or feedback-locked ERPs (e.g., response-locked medial frontal negativity, feedback-locked P3), (5) k = 2 studies investigated dipole sources in a deception task, (6) k = 9 deception studies did not report ERP findings but discussed the overall investigation of physiological parameters in deception studies or (7) were reviews (k = 3), (8) k = 1 study was not on deception although the P3 was investigated (Spapé, Hoggan, Jaccucci, & Ravaja, 2015), (9) k = 2 studies investigated the frontal P3 (Gibbons et al, 2018;Proverbio, Vanutelli, & Adorni, 2013), which conceptually differs from the parietal P3 (Kok, 2001), (10) k = 3 studies were performed in a financial context or in an individual vs.…”
Section: Exclusion Of Primary Studiesmentioning
confidence: 99%
“…Likewise, telling a lie relies on inhibiting the truth and formulating another answer; conflicts have to be monitored and solved ( Gombos, 2006 ; Sip et al., 2008 ). In ERP studies, larger MFN amplitudes occurred for deceptive compared to truthful responses ( Johnson et al., 2004 ; Kireev et al., 2008 ; Leue et al., 2012 ; Gibbons et al., 2018 ; Scheuble and Beauducel, 2020 ). Johnson et al.…”
Section: Introductionmentioning
confidence: 95%